Engineering of Active Sites in Metal‐Organic Frameworks for Friedel–Crafts Alkylation - Lawrence, Arputham Shophia; Sivakumar, Balasubramanian; Rokhum, Samuel Lalthazuala; Biswas, Shyam; Cirujano, Francisco G.; Dhakshinamoorthy, Amarajothi (ChemCatChem, 2025)
Friedel–Crafts alkylation reaction is one of the C─C bond forming reactions catalyzed by homogeneous or heterogeneous catalysts possessing Lewis and Bronsted acids. Metal organic frameworks (MOFs) with Lewis acid/Bronsted acid sites or hydrogen bonding donor sites are potential catalysts to promote the widely employed Friedel–Crafts alkylation to form C─C bonds between arenes and electron‐poor olefins, alcohols, or alkyl bromides. Such acid‐active sites are present either at the organic linkers or inorganic clusters of the crystalline porous framework, resulting in well‐dispersed heterogeneous active sites able to compete with well‐established homogeneous minerals and organocatalysts. The available literature data are grouped based on the nature of active sites. Whenever possible, the comparison of the activity of MOFs with other heterogeneous and homogeneous catalysts is provided to illustrate the possible benefits of MOFs compared to other catalysts. The concluding section provides our views and future developments in this field. Metal Organic Frameworks with Lewis acid/Bronsted acid sites or hydrogen bonding donor sites are potential catalysts to promote the widely employed Friedel–Crafts alkylation to form C─C bonds between arenes and electron‐poor olefins, alcohols, or alkyl bromides.